Вплив екстракту вівса посівного на псування гарбуза при зберіганні - Данченко, Олена Олександрівна; Данченко, Елена Александровна; Danchenko, Olena; Здоровцева, Любов Миколаївна; Здоровцева, Любовь Николаевна; Zdorovtseva, Liubov; Данченко, Микола Миколайович; Данченко, Николай Николаевич; Danchenko, Mykola; Майборода, Данііл Олександрович; Майборода, Даниил Александрович; Maiboroda, Daniil; et al. (Мелітополь: ТДАТУ, 2019)
UK: У статті з’ясовано вплив поверхневої обробки гарбуза екстрактом вівса посівного на процеси псування гарбуза та вміст у його м’якуші низькомолекулярних антиоксидантів (вітаміну С, β-каротину, фенольних сполук) під час тривалого зберігання. Доведено, що така обробка поверхні гарбуза за його тривалого зберігання сприяє кращому збереженню вмісту вітаміну С і фенольних сполук у м’якуші гарбузів, достовірно гальмує їх мікробіологічне псування. Результатами досліджень підтверджено доцільність застосування екстракту вівса для зберігання гарбузів у запропонованому режимі. RU: В статье приведены данные о влиянии обработки тыквы экстрактом овса посевного на процессы порчи тыквы и содержание в её мякоти низкомолекулярных антиоксидантов (витамина С, β-каротина, фенольных соединений) при длительном хранении. Доказано, что такая обработка поверхности тыквы способствует лучшему сохранению содержания витамина С и фенольных соединений в мякоти тыкв, достоверно тормозит их микробиологическую порчу. Результатами исследований подтверждена целесообразность применения экстракта овса при хранения тыквы. EN: By the content of healing substances pumpkin exceeds many other vegetables. However, with prolonged storage of pumpkin, it gradually decreases the content of vitamins and other biologically active substances, and also their surface deterioration is observed. The purpose of this work was to find out the effect of surface treatment of pumpkins with the oat extract on microbial degradation of the pumpkin and the content low molecular weight antioxidants (vitamin C, β-carotene, phenolic compounds) during prolonged storage. Pumpkins of the experimental group before being put into storage were pre-treated with an oat extract. Extraction of flavonoids from oats was carried out with water in the ratio of 1:10 in boiling water bath (60 min). The results of the experiment proved that preliminary processing of pumpkin with oat extract before storage helps to increase the content of vitamin C in pumpkin by 23.5%. Such treatment does not show a likely effect on the dynamics of β-carotene content. During the first two months there was a significant increase in the content of phenolic compounds (by 10.7%, p ≤ 0,05 ) when using oat extract in pumpkins. Subsequent changes in the content of phenolic compounds in pumpkins of the control and experimental series occur unidirectionally with the preservation of the indicated probable difference. Pre-treatment with extract of pumpkin significantly inhibits the microbiological of its damage. Consequently, the use of oats extract for preserving pumpkins in the proposed regime improves the nutritional value of this raw material.
Влияние экстракта овса посевного на порчу тыквы при хранении
The effect of oat etxtract on deterioration of the pumpkin during storage
Keywords: зберігання гарбуза; екстракт вівса; поверхнева обробка; мікробіологічне псування; вітамін С; β-каротин; фенольні сполуки